Specificity of initiation factor preparations from poliovirus-infected cells. - Brown, D (1980)
Crude initiation factor preparations from poliovirus-infected cells stimulated the translation of poliovirus RNA in vitro, but were inactive for the translation of host cell or vesicular stomatitis virus mRNA's. In contrast, similar preparations from either uninfected or vesicular stomatitis virus-infected cells supported the initiation of translation of host cell mRNA's and both viral mRNA's. These results reflect a specific alteration of some components(s) of the initiation factor preparation from poliovirus-infected cells which is consistent with the ability of the virus to inhibit the translation of host cell and vesicular stomatitis virus-directed protein synthesis.